Students' Mathematical Reasoning Ability with Open-Ended Problems in Mathematics Learning (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2025)
Mathematics learning today tends to be closed and mechanistic, limiting students' ability to reason creatively and exploratorily. The role of teachers in building students' reasoning skills is crucial through the problems given. One effective approach to fostering mathematical reasoning is the use of open-ended questions, which allow students to explore multiple solutions rather than following rigid procedures. This study employs a descriptive qualitative approach with a case study method involving 19 fifth-grade students from an elementary school in Bandung Regency. The research focuses on analyzing students' mathematical reasoning skills in solving open-ended problems related to number concepts. Data were collected through direct observation, documentation studies, and interviews with both students and teachers. The findings indicate that open-ended problems encourage students to choose their own methods in problem-solving, fostering deeper mathematical reasoning. Students demonstrated the ability to identify mathematical relationships, justify their answers, and apply reasoning effectively. The results suggest that integrating open-ended problems into mathematics instruction can significantly enhance students' mathematical reasoning skills and promote a more engaging, student-centered learning environment.
Keywords: mathematical reasoning open-ended problems; mathematics learning; problem-solving; elementary school students